2020
DOI: 10.3389/fimmu.2020.550769
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Mediates the Inflammatory Response and LPS Tolerance in Human Monocytes and Macrophages

Abstract: Histone deacetylases (HDACs) are a group of enzymes that control histone deacetylation and bear potential to direct expression of large gene sets. We determined the effect of HDAC inhibitors (HDACi) on human monocytes and macrophages, with respect to their polarization, activation, and their capabilities of inducing endotoxin tolerance. To address the role for HDACs in macrophage polarization, we treated monocytes with HDAC3i, HDAC6i or pan-HDACi prior to polarization into M1 or M2 macrophages using IFNγ or IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
5
31
0
Order By: Relevance
“…On the other hand, animals that experienced repeated LPS exposures might acquire the endotoxin tolerance, resulting in reduced secretions of cytokines ( West and Heagy, 2002 ). It was proved that endotoxin tolerance could be induced in pigs ( Castegren et al., 2013 ), rats ( Santos et al., 2020 ), and human monocyte and macrophage cells ( Ghiboub et al., 2020 ). But whether birds were able to develop the endotoxin tolerance was still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, animals that experienced repeated LPS exposures might acquire the endotoxin tolerance, resulting in reduced secretions of cytokines ( West and Heagy, 2002 ). It was proved that endotoxin tolerance could be induced in pigs ( Castegren et al., 2013 ), rats ( Santos et al., 2020 ), and human monocyte and macrophage cells ( Ghiboub et al., 2020 ). But whether birds were able to develop the endotoxin tolerance was still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC3 is involved in lipopolysaccharide (LPS)-directed cytokine secretion in monocytes and M1 macrophages. HDAC3 disrupts the process by which inflammation-activated M1 macrophages mediate LPS tolerance ( 240 ).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%
“…In humans, the HDAC enzymes family comprises 18 members divided into 4 classes: class I HDACs (HDACs 1–3 and 8), class IIa HDACs (HDACs 4, 5, 7, and 9), class IIb HDACs (HDACs 6 and 10), class III sirtuins (Sirt1–7), and class IV HDACs (HDAC11) [ 12 , 33 , 34 ]. While histone acetyltransferases (HAT) add acetyl groups to lysine residues, thereby permitting TFs binding and subsequent gene expression, histone deacetylases (HDACs) erase histone acetyl residues, leading to chromatin compaction, generally resulting in gene repression [ 33 , 34 ]. However, in contrast to the common role of HDACs for gene repression, treatment with HDAC inhibitors typically leads to a reduction rather than increase in proinflammatory gene expression by immune cells [ 35 ].…”
Section: Advances In Hdac Selective Targeting In Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
“…Genetic depletion of individual HDACs has demonstrated that these proteins mediate specific and unique functions [ 57 ], suggesting therapeutic relevance for selective isoform targeting. While achieving this is a challenge due to conserved structural similarity between HDAC isoforms [ 12 ], HDACi has been reported with selectivity for HDAC1, HDAC2, HDAC3 [ 33 , 58 , 59 , 60 , 61 ], HDAC8 [ 62 , 63 ], HDAC6 [ 64 ], HDAC11 [ 65 ], SIRT1, and SIRT2 [ 66 , 67 ]. However, caution should be taken in interpreting the specificity of the effects of these published inhibitors given the variability of available HDAC assays and the residual dose-dependent effects on other isoforms (Table 1).…”
Section: Advances In Hdac Selective Targeting In Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation